Leading Emerging and Diverse Scientists to Success: Results from LEADS alumni. Issue 1 (10th February 2023) - Rubio, Doris; Norman, Marie K.; Mayowski, Colleen A.; Proulx, Chelsea N.; Karras, Alana; Hausmann, Leslie
Abstract: Purpose: In 2015, the University of Pittsburgh partnered with several Minority Serving Institutions to develop the Leading Emerging and Diverse Scientists to Success (LEADS) Program. LEADS was designed to provide skills development, mentoring, and networking support to early career underrepresented faculty. Method: LEADS included three components: skills training (e.g., grant and manuscript writing and team science), mentoring, and networking opportunities. Scholars completed a pre- and post-test survey and an annual alumni survey that included measures on burnout, motivation, leadership, professionalism, mentoring, job and career satisfaction, networking, and an assessment of their research self-efficacy. Results: Scholars demonstrated a significant increase in their research self-efficacy having completed all the modules ( t = 6.12; P < 0.001). Collectively, LEADS scholars submitted 73 grants and secured 46 grants for a 63% success rate. Most scholars either agreed or strongly agreed that their mentor was effective in helping to develop their research skills (65%) and provided effective counseling (56%). Scholars did experience increased burnout with 50% feeling burned out at the exit survey (t = 1.42; P = 0.16) and 58% reporting feelings of burnout at the most recent survey in 2020 (t = 3.96; P < 0.001). Conclusions: Our findings support the claim that participation in LEADS enhanced critical research skills, provided networking and mentoring opportunities, and contributed to research productivity for scientists from underrepresented backgrounds.